2010
DOI: 10.1111/j.1600-0463.2010.02705.x
|View full text |Cite
|
Sign up to set email alerts
|

Multiplex cytokine profiling in patients with sepsis

Abstract: A major goal for the clinical research in sepsis is mapping the various mediators driving the systemic manifestations of infection. Identifying relevant mediators responsible for the physiological alterations during sepsis may offer diagnostic and therapeutic opportunities. We aimed to explore the novel approach of simultaneously measuring several biomolecules using the multiplex technique and to study its relevance in diagnosing and monitoring septic patients. In 30 patients fulfilling American College of Che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
135
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(153 citation statements)
references
References 32 publications
11
135
0
3
Order By: Relevance
“…Our MCP-1 results are consistent with those reported by Mera et al (2011). Using multiplex cytokine profiling, those authors found that the expression levels of IL-8 and MCP-1 soon after ICU admission were higher in nonsurvivors compared to survivors.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Our MCP-1 results are consistent with those reported by Mera et al (2011). Using multiplex cytokine profiling, those authors found that the expression levels of IL-8 and MCP-1 soon after ICU admission were higher in nonsurvivors compared to survivors.…”
Section: Discussionsupporting
confidence: 83%
“…Five cytokines, RANTES, EGF, VEGF R3, MIP-1δ, and LAP, showed significant and consistent differences between the two groups and were selected for further analysis. Changes in the MCP-1 and IL-6 expression levels were opposite but obviously different between the two groups, consistent with previous reports (Mera et al 2011;Li et al 2014), which demonstrated the value of MCP-1 and IL-6 levels in predicting mortality for patients with sepsis. Therefore, we researched these two cytokines, in addition to the five cytokines mentioned above.…”
Section: Screening Of Plasma Samplessupporting
confidence: 81%
“…In addition, human sepsis results in the upregulation of a number of similar proinflammatory cytokines, including IL-6, IL-8, MCP-1, and MIP-1␣ (53). This begs the question of whether the upregulation of these cytokines is specific to C. albicans-S. aureus infections or whether they are simply activated in response to any polymicrobial peritoneal infection, possibly via simultaneous signaling of innate immunity receptors.…”
Section: Discussionmentioning
confidence: 99%
“…However, mechanical ventilation was not separated as an independent variable in the analysis of cytokine profiles. A more targeted study measured circulating cytokines during the first week after admission in 30 septic patients (480 Immobilization, muscle unloading, mechanical ventilation patient mobilization, respirator weaning FIGURE 2. Specific pathophysiological mechanisms in ICUAW may either evolve in time independently or trigger subsequent pathways to present with phases of myopathy during critical illness.…”
Section: A Cytokine Elevation In Critical Illnessmentioning
confidence: 99%